Artificial Intelligence adoption in micro, small, and medium enterprises: Evidence, barriers, and Islamic ethical reflections for Muslim entrepreneurs in Yogyakarta - Hamid, Edy Suandi; Artha, Bhenu (Journal of Islamic Economics Lariba, 2025)
IntroductionArtificial intelligence is increasingly recognized as a strategic driver of competitiveness and innovation in micro, small, and medium enterprises. Yet the benefits of artificial intelligence adoption are uneven across contexts and often depend on organizational readiness, infrastructure, and ethical governance. This issue is particularly relevant for micro, small, and medium enterprises in Yogyakarta, Indonesia, where many businesses operate with limited digital capability and constrained access to capital. For Muslim entrepreneurs, adoption decisions are further shaped by Islamic business ethics that emphasize trust, transparency, fairness, halal integrity, and social responsibility.ObjectivesThis study examines the importance of artificial intelligence adoption for micro, small, and medium enterprises by synthesizing global evidence and developing a context-sensitive reflection for Muslim entrepreneurs in Yogyakarta, Indonesia. It aims to clarify key benefits, identify persistent barriers, and propose an ethically grounded rationale for responsible adoption.MethodThis study uses an argumentative review approach to analyze peer-reviewed literature on artificial intelligence adoption in micro, small, and medium enterprises. The synthesis is organized into five analytical themes: (1) global evidence on performance impacts, (2) drivers and barriers of adoption, (3) characteristics of micro, small, and medium enterprises in Indonesia and Yogyakarta, (4) opportunities and constraints for implementation in Yogyakarta, and (5) ethical reflections based on Islamic business ethics.ResultsThe review indicates that artificial intelligence adoption can improve productivity, cost efficiency, and decision-making quality in micro, small, and medium enterprises, while also supporting innovation and market competitiveness when integrated with complementary digital capabilities. However, adoption is frequently constrained by limited financial resources, skills gaps, inadequate infrastructure, weak data governance, and uncertainty about return on investment. In Yogyakarta, these constraints are reinforced by informal business structures and uneven digital readiness, suggesting that adoption pathways must be incremental, affordable, and supported by capability development.ImplicationsThis study highlights that artificial intelligence adoption for micro, small, and medium enterprises in Yogyakarta should be approached as a socio-technical and ethical decision, not merely a technical investment. Practical implications include the need for targeted training, affordable artificial intelligence services, and governance practices that strengthen consumer trust.Originality/NoveltyThis study contributes a contextual and ethically grounded synthesis by linking global artificial intelligence adoption evidence with the realities of micro, small, and medium enterprises in Yogyakarta and the normative considerations of Muslim entrepreneurship in Indonesia.